Comparison of handheld ultrasound and automated breast ultrasound in women recalled after mammography screening. (May 2017) - Hellgren, Roxanna; Dickman, Paul; Leifland, Karin; Saracco, Ariel; Hall, Per; Celebioglu, Fuat
Background: Automated breast volume scanner (ABVS) is an ultrasound (US) device with a wide scanner that sweeps over a large area of the breast and the acquired transverse images are sent to a workstation for reconstruction and review. Whether ABVS is as reliable as handheld US is, however, still not established. Purpose: To compare the sensitivity and specificity of ABVS to handheld breast US for detection of breast cancer, in the situation of recall after mammography screening. Material and Methods: A total of 113 women, five with bilateral suspicious findings, undergoing handheld breast US due to a suspicious mammographic finding in screening, underwent additional ABVS. The methods were assessed for each breast and each detected lesion separately and classified into two categories: breasts with mammographic suspicion of malignancy and breasts with a negative mammogram. Results: Twenty-six cancers were found in 25 women. In the category of breasts with a suspicious mammographic finding (n = 118), the sensitivity of both handheld US and ABVS was 88% (22/25). The specificity of handheld US was 93.5% (87/93) and ABVS was 89.2% (83/93). In the category of breasts with a negative mammography (n = 103), the sensitivity of handheld US and ABVS was 100% (1/1). The specificity of handheld US was 100% (102/102) and ABVS was 94.1% (96/102). Conclusion: ABVS can potentially replace handheld US in the investigation of women recalled from mammography screening due to a suspicious finding. Due to the small size of our study population, further investigation with larger study populations is necessary before the implementation of such practice.